2009
DOI: 10.3109/02699200903281739
|View full text |Cite
|
Sign up to set email alerts
|

Inflexibility as an interactional phenomenon: Using conversation analysis to re-examine a symptom of autism

Abstract: Many accounts of autism spectrum disorder (ASD) imply that the condition's behavioural 'symptoms' are direct reflexes of underlying deficits. In doing so, however, they invariably overlook the social contexts in which symptomatic behaviours occur and are identified as pathological. This study addresses this issue, using conversation analysis (CA) to examine the emergence of inflexibility, a behavioural trait symptomatic of ASD, during play involving an adult and diagnosed child. We argue that 'inflexibility' i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…Supporting autistic people requires flexibility between autistics and communication partners (Muskett et al, 2010). For example, autistic children tend to build more skills when their parents understand and accept them (Kapp et al, 2013; Oppenheim and Koren-Karie, unpublished).…”
Section: Person-environment (Social) Interactionmentioning
confidence: 99%
“…Supporting autistic people requires flexibility between autistics and communication partners (Muskett et al, 2010). For example, autistic children tend to build more skills when their parents understand and accept them (Kapp et al, 2013; Oppenheim and Koren-Karie, unpublished).…”
Section: Person-environment (Social) Interactionmentioning
confidence: 99%
“…Muskett et al. (2010) use a conversation analytic approach to study the commonly observed ASD symptom of inflexibility.…”
mentioning
confidence: 99%
“…CA has been used widely in research on various interactional aspects of autism (Dickerson et al 2007; Korkiakangas et al 2012; Marlaire and Maynard 1990; Maynard 2005; Maynard and Marlaire 1992; Muskett et al 2010; Sterponi and Fasulo 2010; Stribling et al 2007; Turowetz 2015), as well as schizophrenia (McCabe 2009), aphasia (Goodwin 2003; Wilkinson et al 2007) and learning disabilities (Antaki and Wilkinson 2012). …”
Section: Methodsmentioning
confidence: 99%